2011
DOI: 10.1590/s1806-66902011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Produção de alface em NFT e Floating aproveitando água salobra e o rejeito da dessalinização

Abstract: Resumo -), um efluente do processo de dessalinização. Estas águas foram combinadas em seis tratamentos resultantes da sua utilização alternada para preparar a solução nutritiva (SN) e/ou substituir as perdas por evapotranspiração (ETc). O experimento foi conduzido em casa de vegetação na região semiárida de Pernambuco, utilizando 48 unidades experimentais em blocos casualizados em esquema fatorial 6x2 com quatro repetições. O rendimento da alface (massa de matéria fresca) foi maior nas condições do Floating. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
(22 reference statements)
0
12
0
8
Order By: Relevance
“…Studying the performance of lettuce cultivars subjected to different salinity levels of the irrigation water, Oliveira et al (2011) observed that growth parameters decreased linearly with the increase in salinity, which was also found by Soares et al (2010), Santos et al (2011) and Alves et al (2011).…”
Section: Introductionmentioning
confidence: 78%
“…Studying the performance of lettuce cultivars subjected to different salinity levels of the irrigation water, Oliveira et al (2011) observed that growth parameters decreased linearly with the increase in salinity, which was also found by Soares et al (2010), Santos et al (2011) and Alves et al (2011).…”
Section: Introductionmentioning
confidence: 78%
“…In Brazil, this vegetable has great economic and social importance, because its production has a relatively low cost, besides a high demand for labor, allowing small properties to cultivate it, thus generating jobs and income (Alves et al, 2011;Dias et al, 2011;Lúcio et al, 2011;Santos et al, 2011;Paulus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A few promising results have been achieved for the rational use of brackish water in the Nutrient Film Technique (NFT) hydroponic system (Santos et al, 2010(Santos et al, , 2011Soares et al, 2010Soares et al, , 2015Alves et al, 2011;Paulus et al, 2012;Bione et al, 2014;Lira et al, 2015), which can open a new perspective for hydroponics as an economic alternative, provided that brackish water is available. In Brazil, the main focus of these studies is the semiarid region, where brackish water is relatively frequent in the underground reserves, for constituting one of the main causes of abandonment of the various wells drilled with public or private resources (Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, systems such as Floating and Deep Film Technique (DFT) are promising for the rural communities of the semiarid region, where interruptions in water supply are frequent. In these systems, plant roots remain submerged in the nutrient solution (Zanella et al, 2008;Santos et al, 2011); therefore, they will only suffer with the effects of recirculation if it is so prolonged that the solution level is reduced. Due to this advantage, such systems assume less frequent recirculations compared with NFT, in which irrigation is usually performed in intervals of 15 min.…”
Section: Introductionmentioning
confidence: 99%